On Cuscuta reflexa Roxb. in Namkum, Ranchi, Bihar - Prasad, U. N. (Indian Forester, 1966)
The paper deals mainly with the parasitism and the wide range of host-species of Cuscuta rejlexa Roxb, in Namkum, Ranchi. The parasitism in this case is of ’diffuse type’. Even though it is chiefly parasitic on woody and arborescent species of the dicotyledons; its record on a number of herbaceous plants belonging to the Compositae, the Cyperaceae and the Gramineae is of great interest.